Tying Devices to Mitigate Pounding of Adjacent Building Blocks - Masmoum, M. S.; Alama, M. S. A. (Engineering, Technology & Applied Science Research, 2020)
Adjacent building blocks separated by thermal expansion joints are vulnerable to pounding during earthquakes. The specified Saudi building code minimum separation may be very large and does not necessarily eliminate pounding forces. This research discusses the feasibility of tying the adjacent building blocks with simple devices to mitigate structural pounding when separated by thermal joints. Six and twelve-story moment resistance frames of intermediate ductility were designed for seismic loads of moderate risk. The seismic response was studied for frames with variable separation distances in three cases related to thermal joint, code minimum separation, required separation to eliminate pounding force, and in a fourth case in which the tying device was used along with thermal separation. A linear elastic model was used to model the assigned gap links between the adjacent building blocks. The tying device was modeled with a tension-only hook element. Four normalized earthquake records were used with inelastic-time history analysis to assess the seismic response of the adjacent building blocks. The proposed tying devices reduced successfully the pounding forces by 40% to 60% for adjacent building blocks with installed thermal separations. Building damage as observed from damage index and the hysteretic response was not influenced by the pounding force, indicating that the tying may be used on existing buildings with thermal separation as a partial mitigation technique to reduce the pounding hazard in such cases. Further improvement on the tying device will increase the mitigation of the pounding hazard.